SOURCES OF STRESS AND COPING STRATEGIES FOR LEADERS IN FACING THE MERGER PROCESS AT THE RESEARCH CENTER MEDAN PALM - Fatimahhakki Salsabela; Nur Aisyah; Sjahril Effendy (RADJA PUBLIKA, 2023)
Entering the era of free trade, business competition between companies is getting tighter. This condition requires companies to always develop company strategies so that they can survive or develop further. Therefore, companies need to develop an appropriate strategy in order to survive, develop and be competitive. One strategy that can be carried out by companies is by merger. A merger is the process of combining two entities with one of them remaining under its entity name, while the other disappears. Margers can affect organizational members in many ways, resulting in diverse emotional experiences, which will likely influence individual behavior and determine the success of managing a merger. Negative emotions experienced by company leaders are stress, fear, worry, and insecurity, mainly triggered by ambiguity regarding their future roles and the roles of their subordinates in the newly joined organization. Work stress can affect the merger process and reduce work productivity, so coping is needed to deal with these problems. Coping carried out can be different. The number of respondents in this study was 4 respondents with qualifications for the positions of deputy head, section head and sub-section head. The research method used in this research is a qualitative method. The research results showed that each respondent showed different responses in dealing with sources of stress and the coping strategies they used. This source of stress has an impact on the success of the merger process.